COMPONENTS OF THE TOTAL POWER LOSSES IN THREE-PHASE ENERGY SUPPLY SYSTEMS WITH SYMMETRIC SINUSOIDAL VOLTAGE SOURCE - Zhemerov, George G.; Tugay, D. V. (National Technical University "Kharkiv Polytechnic Institute" and Аnatolii Pidhornyi Institute of Power Machines and Systems of NAS of Ukraine, 2015)
Purpose. Three-phase energy supply system with a symmetrical resistive load operates in mode with the highest possible efficiency in a case of zero instantaneous reactive power and the absence of pulsations instantaneous active power. When load parameters are changed, three-phase energy supply system starts to operate in a mode with additional energy losses. The goal of the paper is to determinate the relations between the components of additional losses and their rezone. Methodology. We have applied the modern theory of instantaneous active and reactive power, the graphical filling complex branched energy supply system of simplified design scheme, the theory of electrical circuits, computer Matlab-simulation. Results. We have developed an universal relation to determine the components of total power loss in the three-phase supply systems with symmetrical three-phase sinusoidal voltage source and any possible load. Further verification of this relation in the Matlab-model of three-phase energy supply system shows its high accuracy. Originality. For the first time, we have carried out relation between RMS reactive and RMS active power instantaneous pulsation and the corresponding components of additional losses. Consequently it becomes possible to offer a unique method of weighting evaluation. Practical value. We have developed position for detecting the causes of additional losses in three-phase supply systems with symmetrical sinusoidal voltage source, as well as to substantiate the correctness of the choice of filter-compensating device. We have developed a Matlab-model which allows to investigate the energy efficiency of three-phase energy supply system and to calculate the components of additional power losses of any possible reasons for their occurrence.